2015
DOI: 10.1007/s10552-015-0608-2
|View full text |Cite
|
Sign up to set email alerts
|

Diet and risk of adult leukemia: a multicenter case–control study in China

Abstract: Our findings suggest that diets rich in vegetables and adequate amount of milk reduce the risk of adult leukemia, whereas diets preferring fat, deep-fried, and smoked foods increase the risk in Chinese populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 31 publications
(76 reference statements)
1
10
0
Order By: Relevance
“…Interaction between MTHFR/TS polymorphisms and dietary folate intake on leukemia susceptibility We previously reported that higher dietary folate intake was inversely associated with adult leukemia risk [7]. This study is the first report so far to examine the risks of adult leukemia with polymorphisms of folate pathway genes in conjunction with dietary folate intake.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…Interaction between MTHFR/TS polymorphisms and dietary folate intake on leukemia susceptibility We previously reported that higher dietary folate intake was inversely associated with adult leukemia risk [7]. This study is the first report so far to examine the risks of adult leukemia with polymorphisms of folate pathway genes in conjunction with dietary folate intake.…”
Section: Discussionmentioning
confidence: 66%
“…Study design and participants The study design has been reported in detail elsewhere [7]. Briefly, a hospital-based casecontrol study was conducted at three major public hospitals in southeast and northeast China between April 2008 and August 2013, namely the First and the Second Affiliated Hospitals of Zhejiang University in Hangzhou, Zhejiang Province, and the First Hospital of China Medical University in Shenyang, Liaoning Province.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Continual dairy consumption, compared to a carbohydrate-based diet, may decrease systemic inflammation through a significant decrease in the expression of IL-1β and IL-6 and an improvement of hepatic steatosis index scores 13 14 . A recent clinical multicenter case-control study documented that adequate amounts of milk reduced the risk of malignant lymphoproliferative diseases and adult leukemia 15 .…”
mentioning
confidence: 99%